Perilipin LDP1 coordinates lipid droplets formation and utilization for appressorium‐mediated infection in Magnaporthe oryzae. (27th April 2020) - Cai, Xuan; Yan, Jingjing; Liu, Caiyun; Xing, Junjie; Ren, Zhiyong; Hendy, Ahmed; Zheng, Lu; Huang, Junbin; Chen, Xiao‐Lin
Summary: Lipid droplets (LDs) serve as one of the major reservoirs in conidia of Magnaporthe oryzae and are quickly utilized during appressorium formation. Here, we identified a gene, LDP1, encoding a perilipin that is important for LD formation and utilization during appressorium maturation. LDP1 is highly expressed in conidium and immature appressorium. Disruption mutants of LDP1 were significantly reduced in virulence, due to appressorial turgor reduction and difficulty in penetration. LDs were significantly reduced in the Δ ldp1 mutant, indicating LDP1 was required for LDs formation. LDP1 was colocalized with the LDs in conidium and immature appressorium but was gradually separated during appressorium maturation. A typical intracellular triacylglycerol lipase, TGL1‐2, was clearly separated with LDs in conidium and immature appressorium but was well colocalized with LDs during appressorium maturation. The subcellular localization of TGL1‐2 was affected by LDP1. These data suggested that LDP1 was bound to LDs for protecting from utilization in conidia and at the early appressorium stage but was separated from LDs for lipase entering and degradation. LDP1 was phosphorylated by CPKA at Thr96, which was essential for its localization and functions. These data indicate perilipin LDP1 can coordinate LD formation and utilization for appressorium‐mediated infection of M . oryzae .